Composite solid electrolyte of sulfide coated with hydride based on mechanical grinding and preparation method and application of composite solid electrolyte

Through mechanical grinding, hydride LiBH4 and sulfide Li10GeP2S12 are combined to form a composite solid electrolyte with hydride coated sulfide, which solves the problems of unstable contact of sulfide electrolyte at the lithium metal interface and narrow electrochemical window, and realizes all solid state The high electrochemical performance and long cycle life of lithium metal batteries.

CN119400938APending Publication Date: 2025-02-07RES INST OF ZHEJIANG UNIV TAIZHOU +1

Patent Information

Application Number
CN202411786677.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The sulfide-based solid electrolytes have unstable contacts at the lithium metal interface, narrow electrochemical windows, and prone to adverse side reactions during charging and discharging, which limits their large-scale application in all-solid-state battery systems.

Method used

Hydride LiBH4 and sulfide Li10GeP2S12 are compounded through mechanical grinding to form a composite solid electrolyte with hydride coated sulfide, improving its interface stability and electrochemical properties.

Benefits of technology

This method significantly reduces the adverse side reaction between sulfide and electrode, improves the interface stability and cycle life of the electrolyte, and improves the electrochemical performance and energy density of all-solid lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400938A_ABST
    Figure CN119400938A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydride-coated sulfide composite solid electrolyte based on mechanical grinding. The preparation method comprises the following steps: (1) mixing two solid electrolytes Li10GeP2S12 and LiBH4 to form a primary composite electrolyte; and (2) carrying out mechanical grinding on the composite electrolyte in a glove box under the protection of an argon atmosphere so as to form the composite solid electrolyte with LiBH4 coated with Li10GeP2S12. The invention also discloses the hydride-coated sulfide composite solid electrolyte prepared by the preparation method and an application of the hydride-coated sulfide composite solid electrolyte. According to the preparation method, the surfaces of sulfide particles can be effectively coated with the hydride, and the original electrochemical performance of the composite solid electrolyte is maintained to the greatest extent, so that the problems that the sulfide generates adverse side reaction with an electrode in the charging and discharging process and is easy to decompose under high voltage and the like can be greatly reduced; the assembled lithium metal symmetric battery and the all-solid-state lithium metal battery both show excellent electrochemical performance and relatively long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy materials, and in particular relates to a composite solid electrolyte of hydride-coated sulfide based on mechanical grinding, and a preparation method and application thereof. Background Art

[0002] After decades of rapid development, rechargeable lithium-ion batteries have been widely used in various markets. However, traditional lithium batteries face challenges such as flammable electrolytes, limited chemical stability, and lithium dendrite growth. In order to completely solve a series of problems existing in the system and hope to further improve the energy density of the battery, all-solid-state batteries have received more and more attention. Solid electrolytes have become a very promising choice to replace traditional flammable organic electrolytes due to their inherent safety and potential high energy density. Sulfide-based solid electrolytes have lithium ion conductivity comparable to that of liquid electrolytes at room temperature and show broad application prospects. For example, the Chinese patent with publication number CN112820935A discloses that the solid electrolyte is a solid electrolyte with sulfide as the lithium-conducting core, including sulfide and a polymer matrix. And the Chinese patent with publication number CN118610556A discloses that a composite material including metal sulfide and carbon quantum dots is used as an inorganic filler in a polymer solid electrolyte.

[0003] However, problems such as the instability of the interface contact between sulfide-based solid electrolytes and lithium metal and the relatively narrow electrochemical window of the electrolyte itself still limit their large-scale production and application in the field of energy storage. Summary of the invention

[0004] The purpose of the present invention is to provide a composite solid electrolyte of hydride coated with sulfide based on mechanical grinding, and a preparation method and application thereof. The preparation method can effectively coat the hydride on the surface of the sulfide particles and maintain the original electrochemical properties of the composite solid electrolyte to the greatest extent, thereby greatly reducing the problems of the sulfide producing adverse side reactions with the electrode during the charging and discharging process and being easily decomposed under high voltage. The assembled lithium metal symmetric battery and all-solid-state lithium metal battery both show excellent electrochemical properties and a long cycle life.

[0005] The present invention provides the following technical solutions:

[0006] A method for preparing a composite solid electrolyte of hydride-coated sulfide based on mechanical grinding, the preparation method comprising the following steps:

[0007] (1) Two solid electrolytes Li 10 GeP2S 12 Mix with LiBH4 to form a preliminary composite electrolyte;

[0008] (2) The composite electrolyte was protected in an argon atmosphere in a glove box and mechanically ground to form LiBH4-coated Li 10 GeP2S 12 Composite solid electrolyte.

[0009] The present invention uses a sulfide solid electrolyte (Li2O3) whose room temperature ion conductivity is comparable to that of a liquid electrolyte. 10 GeP2S 12 ) as the main component of the electrolyte, so as to meet the required performance of the battery in the solid-state system; a hydride solid electrolyte (LiBH4) which is very stable, soft, and has excellent ductility and dispersibility for the lithium metal negative electrode is selected as the composite component of the solid-state electrolyte.

[0010] The design idea of ​​the composite solid electrolyte of hydride coated sulfide described in the present invention is that as a relatively ideal traditional solid electrolyte, sulfide solid electrolyte has very excellent ionic conductivity at room temperature. However, the problems such as poor interface contact between sulfide electrolyte and lithium metal negative electrode, narrow electrochemical window, and easy generation of adverse side reactions during the cycle process seriously restrict its large-scale application in all-solid-state battery systems. Although the hydride solid electrolyte cannot become the main component of the electrolyte in the solid-state system due to its poor ionic conductivity, its excellent chemical stability and good ductility to the lithium metal negative electrode can also ensure a dense and good interface contact between the electrolyte and the electrode. Therefore, a small amount of hydride is used to coat and modify the sulfide, thereby greatly improving the interface problem of the solid electrolyte while maintaining high ionic conductivity, and realizing the production and application of the electrolyte in the all-solid-state battery system.

[0011] The design principle is that although sulfide solid electrolytes have an ionic conductivity comparable to that of liquid electrolytes at room temperature, they have poor chemical stability with the lithium metal negative electrode during the charge and discharge process, and are prone to side reactions that are not conducive to the battery life. At the same time, their narrow electrochemical window and easy decomposition at higher voltages also limit the application of sulfide solid electrolytes; while hydride solid electrolytes have very high chemical stability to lithium metal and a very high electrochemical window, which allows them to be coated on the surface of sulfide electrolyte particles to form a denser composite solid electrolyte, which can significantly reduce the interface resistance between electrolyte grains and between the electrolyte and the electrode, effectively improving the stability of the composite solid electrolyte and greatly increasing the cycle life of the all-solid-state battery.

[0012] In step (1), the Li 10 GeP2S 12 It is compounded with LiBH4 in a molar ratio of 1:2.

[0013] In step (2), the mechanical grinding time is at least 30 minutes.

[0014] The present invention will Li 10 GeP2S 12 It is mixed with LiBH4 in a molar ratio of 1:2 and fully ground for more than 30 minutes under the protection of an argon atmosphere in a glove box to form a hydride-coated sulfide composite solid electrolyte, which is a composite solid electrolyte that can significantly improve the stability of the lithium metal negative electrode while maintaining the excellent ionic conductivity of the sulfide solid electrolyte.

[0015] The solid electrolyte Li 10 GeP2S 12 The sulfide electrolyte with a particle size of 1 to 5 microns can significantly reduce the resistance between electrolyte grains.

[0016] The present invention also provides a composite solid electrolyte of hydride-coated sulfide obtained according to the above preparation method.

[0017] The present invention also provides an application of the above-mentioned hydride-coated sulfide composite solid electrolyte in assembling a lithium metal symmetric battery and an all-solid-state lithium metal battery.

[0018] The solid-state lithium metal battery comprises a ternary positive electrode composite material containing a composite solid-state electrolyte of a hydride-coated sulfide.

[0019] The ternary positive electrode composite material comprises NCM811 ternary positive electrode material, LiBH4 coated Li 10 GeP2S 12 Composite solid electrolyte and conductive carbon black.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a composite solid electrolyte of hydride coated with sulfide based on mechanical grinding. The composite solid electrolyte is formed by grinding and compounding two solid electrolytes of hydride and sulfide to form a composite solid electrolyte in which hydride is coated on the surface of sulfide particles, so that the hydride is effectively coated on the surface of sulfide particles during the grinding process, and the original electrochemical properties of the composite solid electrolyte are maintained to the greatest extent, thereby greatly reducing the problems of adverse side reactions between sulfide and electrodes during the charge and discharge process and easy decomposition under high voltage. The preparation process steps are simple and effective, and the production efficiency is high.

[0022] The hydride-coated sulfide composite solid electrolyte prepared by mechanical grinding in the present invention exhibits good compactness and ductility, achieves good interface contact with the lithium metal negative electrode and chemical stability with the high-voltage electrode, and the assembled lithium metal symmetric battery and all-solid-state lithium metal battery both show relatively excellent electrochemical performance and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used to represent the same components throughout the accompanying drawings. In the accompanying drawings:

[0024] Figure 1 A schematic diagram of the preparation process of a hydride-coated sulfide composite solid electrolyte provided in an embodiment of the present invention;

[0025] Figure 2 An X-ray diffraction pattern of a composite solid electrolyte of hydride-coated sulfide provided in an embodiment of the present invention;

[0026] Figure 3 Scanning electron microscope images of the hydride-coated sulfide composite solid electrolyte provided in an embodiment of the present invention at different magnifications: (a) is a morphology image magnified 2000 times, and (b) is a morphology image magnified 10000 times;

[0027] Figure 4 A critical current density test diagram of a composite solid electrolyte of hydride-coated sulfide provided in an embodiment of the present invention;

[0028] Figure 5 A graph showing the electrochemical performance cycle test of an all-solid-state battery assembled with a hydride-coated sulfide composite solid electrolyte provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0029] Various additional advantages and benefits will become apparent to those of ordinary skill in the art from a reading of the following detailed description of the preferred embodiments.

[0030] Specifically, the preparation method and application of the hydride-coated sulfide composite solid electrolyte provided in the embodiment of the present invention include:

[0031] (1) Figure 1 As shown, the preparation process of the composite electrolyte specifically includes:

[0032] Li was heated in a glove box filled with inert gas (argon, 99.999%) and isolated from air (H2O < 0.1 ppm, O2 < 0.1 ppm). 10 GeP2S 12The powder of LiBH4 was weighed and mixed in a molar ratio of 1:2 to form a preliminary composite electrolyte; the prepared electrolyte was then placed in a mortar and ground for 30 minutes until the powder was evenly composited, and finally LiBH4 coated Li 10 GeP2S 12 Composite solid electrolyte materials.

[0033] The present invention provides a composite solid electrolyte based on mechanical grinding of hydride-coated sulfide, by mechanical grinding of Li 10 GeP2S 12 With LiBH4, a composite solid electrolyte consisting of hydride-coated sulfide is formed in an inert gas atmosphere.

[0034] like Figure 2 As shown in the figure, the X-ray diffraction peaks of the ground composite solid electrolyte correspond well to those of the original components, and the original properties of the electrolyte are maintained during the composite process. Figure 3 As shown, scanning electron microscopy shows that the composite solid electrolyte exhibits good density and uniformity, greatly reducing the interface resistance between electrolyte particles and between electrolyte and electrodes, and effectively optimizing the lithium ion transmission path.

[0035] (2) Battery assembly and testing of composite electrolyte critical current density, including:

[0036] Assembling LiBH4-coated Li using solid-state battery molds in a glove box 10 GeP2S 12 The lithium metal symmetric battery with a composite solid electrolyte is made according to the symmetrical structure of lithium / solid electrolyte / lithium. First, a lithium metal foil is placed at the bottom of the mold, and then 100 mg of the composite solid electrolyte is poured in. Then another lithium metal foil is placed on top of the electrolyte to complete the battery assembly. A pressure of 10 MPa is then applied to the battery mold to form a dense structure of the electrolyte and maintain close contact between the lithium sheet and the electrolyte. The above processes are all carried out under the protection of an inert gas (argon, 99.999%).

[0037] The assembled lithium metal symmetrical battery was connected to the Blue Electric test system, and the charge and discharge test was started from a current density of 0.1C. During the test, the current size was continuously increased at a rate of 0.1C per hour until the battery failed due to a short circuit during the cycle, and the maximum critical current density of the battery was recorded.

[0038] (3) Assembly and testing of all-solid-state batteries with composite electrolytes, including:

[0039] Assembling LiBH4-coated Li using solid-state battery molds in a glove box 10 GeP2S12 The composite solid electrolyte all-solid-state battery, according to the full battery structure of lithium sheet / solid electrolyte / positive electrode material, first place the lithium metal foil at the bottom of the mold, then pour in 100mg of composite solid electrolyte and press the lithium sheet and composite electrolyte at a pressure of 10 tons MPa, and then pour in 10mg of the prepared ternary positive electrode composite material to form a complete full battery structure and complete the battery assembly. Finally, a pressure of 10MPa is applied to the battery mold to make the positive electrode material form a dense structure and maintain close contact with the electrolyte. The above processes are all carried out under the protection of inert gas (argon, 99.999%).

[0040] The ternary cathode composite material used is NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) ternary cathode material, LiBH4 coated Li 10 GeP2S 12 The composite solid electrolyte and conductive carbon black are mixed in a mass ratio of 8:4:1 and ground in a mortar for 30 minutes. The above process is carried out under the protection of inert gas (argon, 99.999%).

[0041] The assembled all-solid-state battery is connected to the Blue Electric test system and charged and discharged at a current density of 0.1C. The voltage window is set to 2.5V-4.2V until the battery fails due to short circuit or there is a significant decrease in capacity. The battery capacity, retention rate, and number of cycles during the charge and discharge process are recorded.

[0042] The electrochemical performance test results show that: Figure 4 As shown, the composite solid electrolyte has a 2.9 mA cm -2 The high critical current density has excellent ability to inhibit the growth of lithium dendrites; Figure 5 As shown, the assembled all-solid-state battery has a capacity of 67.5 mAh g -1 The initial capacity of the battery was 2.387 W·m-1 and the charge-discharge cycle was more than 50 times without rapid capacity decay and short circuit. It also showed a high specific capacity and life, which verified that the composite solid-state electrolyte can effectively match the lithium metal negative electrode with higher energy density and the ternary positive electrode material.

[0043] Although the preferred embodiments of the present invention have been disclosed for illustrative purposes, those skilled in the art will appreciate that various modifications, additions and substitutions are possible, and thus, the scope of the present invention should not be limited to the above embodiments.

Claims

1. A method for preparing a composite solid electrolyte of hydride-coated sulfide based on mechanical grinding, characterized in that: The preparation method comprises the following steps: (1) Two solid electrolytes Li 10 GeP2S 12 Mix with LiBH4 to form a preliminary composite electrolyte; (2) The composite electrolyte was protected in an argon atmosphere in a glove box and mechanically ground to form LiBH4-coated Li 10 GeP2S 12 Composite solid electrolyte.

2. The method for preparing a composite solid electrolyte of hydride-coated sulfide based on mechanical grinding according to claim 1, characterized in that: In step (1), the Li 10 GeP2S 12 It is compounded with LiBH4 in a molar ratio of 1:

2.

3. The method for preparing a composite solid electrolyte of hydride-coated sulfide based on mechanical grinding according to claim 1, characterized in that: In step (2), the mechanical grinding time is at least 30 minutes.

4. The method for preparing a composite solid electrolyte of hydride-coated sulfide based on mechanical grinding according to claim 1, characterized in that: The solid electrolyte Li 10 GeP2S 12 A sulfide electrolyte having a particle size of 1 to 5 microns.

5. A composite solid electrolyte of hydride-coated sulfide obtained according to the preparation method according to any one of claims 1 to 4.

6. An application of the hydride-coated sulfide composite solid electrolyte according to claim 5 in assembling a lithium metal symmetric battery and an all-solid-state lithium metal battery.

7. The use according to claim 6, characterized in that: The solid-state lithium metal battery comprises a ternary positive electrode composite material containing a composite solid-state electrolyte of a hydride-coated sulfide.

8. The use according to claim 7, characterized in that: The ternary positive electrode composite material comprises NCM811 ternary positive electrode material, LiBH4 coated Li 10 GeP2S 12 Composite solid electrolyte and conductive carbon black.

Citation Information

Patent Citations

  • Novel battery based on sulfide solid-state electrolyte

    CN112820935A

  • Metal sulfide-based composite material, preparation method thereof, solid electrolyte and application

    CN118610556A

Cited By

  • Sulfide / hydroboron composite solid electrolyte with surface LiCl coating layer and preparation method and application of sulfide / hydroboron composite solid electrolyte

    CN121546133A